Análise paramétrica de vibrações em laje nervurada devido às ações humanas - Costa, Yuri Cláudio Vieira da (2012)
In Fortaleza city , the use of ribbed concrete slabs in multi-storey buildings is widesp read. These buildings are designed to many different p urposes, such as gy ms, sup ermarkets, p arking and residential units. This floor slab ty p e has ap p eared as an alternative to overcome longer floor sp ans and reduce self-weight of structures. As the structures evolved, p eop le's behavior has also been adap ting to modernity . Nowaday s it is very common to use residential p ortable fitness equip ment such as stationary bikes, mini elastic beds, among others. It is well-known the dissemination of gy m centers in shopp ing centers, in little commercial centers and even in residential buildings. M oreover, the aerobic activity is not only that can generate vibrations in floor slabs. Other activities can cause vibrations too, such as a simp le meeting between friends to watch a soccer game, children p lay ing, among others. The vibrations in floor slab can cause discomfort on p eop le, doubts about the structure safety , p eeling floors and, dep ending on vibration intensity , collap se risk. Therefore, the objective of this study is to analy ze the dy namic behavior of ribbed concrete floor slabs when submitted to rhy thmic human actions. For this p urp ose, p arametric studies are conducted, using the software SAP 2000 - v.14 (CSI, 2008). The ribbed floor slabs are modeled by three-dimensional solid finite elements, in order to get the eccentricity between the structural elements (table floor, ribbing, and edge beam). The results are comp ared between itself and the analy sis static resp onses of these floor slabs using loads p rop osed by Brazilian code. In addition, dy namic results are comp ared with normative data p rovided by NBR 6118 (ABNT, 2003) in relation to natural frequencies and international standards about to human comfort. The analy ses show that ribbed floor slabs are subjected to high p eaks acceleration and velocity.